Influence of weather parameters on the incidence of sucking pests of rice fallow blackgram in north coastal Andhra Pradesh - Swathi, K; Seetharamu, P; Dhurua, S; Suresh, M; Govindarao, S (Indian Journal of Plant Protection, 2020)
A field experiment was conducted at Agricultural College, Naira during rabi, 2017-2018 to study the seasonal incidence and influence of weather parameters on the population of sucking pests viz., whiteflies (Bemisia tabaci Gennadius) and thrips (Caliothrips indicus Bagnall) in rice fallow blackgram with a cultivar of LBG-752. The incidence of whiteflies was observed throughout the crop period but the peak population of 406 whiteflies per 50 plants was recorded during 5th standard week, while the incidence of thrips was also observed throughout the crop growth period with the peak population of 500 thrips per 50 plants during 2nd standard week. Correlation studies between the weather factors and whitefly population showed non-significant negative correlation with minimum temperature (r = -0.507), evening relative humidity (r = -0.126) and wind velocity (r = -0.437) while maximum temperature (r = 0.281), morning relative humidity (r = 0.536) and mean sunshine hours (r = 0.284) showed non-significant positive correlation. The population of thrips showed non-significant negative correlation with maximum temperature (r = -0.71) and mean sunshine hours (r= -0.180) while minimum temperature (r = -0.593) had negative significant effect, whereas morning and evening relative humidity (r= 0.485, r= 0.330) and wind velocity ( r =0.096) showed non-significant positive correlation with thrips population. Overall, the results revealed that weather parameters viz., temperature, relative humidity, sunshine and wind velocity were factors limiting the build-up of sucking pests population in rice fallow blackgram